Fiscal transparency puzzle and electoral institutions: applying a 3Ds approach for tracking the action cycle in Egypt. Issue 3 (2nd July 2016) - Abdellatif, Lobna; Hassan, Mazen; Youssef, Noha; Zaky, Mohamed
ABSTRACT: This article aims at contributing to the discussion on the fiscal transparency puzzle. The authors challenge the idea that fiscal disclosure can directly increase fiscal accountability. Using an original data set at the level of individual members of parliament (MPs) in the Egyptian parliament, constructed from content analysis of budgetary discussions during the period 2000–10, it is shown that political incentives determined by a majoritarian electoral system curbed the willingness to check government fiscal behaviour, even among opposition MPs. This is because MPs still favoured pork-barrel behaviour to boost their re-election chances. Moreover, fiscal data disclosed could not be communicated to voters and the opposition showed a relatively higher avoidance against fiscal disclosure. The authors conclude that the electoral system is a dominant factor in shaping the final effect of transparency given its influence on the structure of political incentives.